A techno-economic approach for quantifying the maximum allowable wind generation in the Luzon grid - De Guzman, Gilbert M. (2011)
In this project, we determined the maximum allowable penetration of wind power generation in the Luzon Grid by taking into account the load-following and frequency-regulating (LFFR) reserve level requirements. We used the hourly load and wind data of the Luzon Grid in 2009. The current deterministic method used by the Philippine regulator sets the LFFR reserve requirement at 2.8% of the forecasted load for the hour. Using probabilistic methods, we determined the LFFR reserve that would result in frequency violations for only 0.01% of the total time. From this project, we were able to draw three significant conclusions. First, in 2009, the optimal LFFR reserve requirement should have been only 1.35% instead of 2.8% of the forecasted load. Second, using the available LFFR reserve in 2009, the maximum wind penetration that could have been achieved was 15.7% compared to the 0.47% wind penetration at the time. Last, if the target is least cost power generation, the optimal wind penetration is 0% because of the high cost of wind generation and the corresponding increase in the LFFR reserve requirement.